Self Branding Mobilephone Photographer in Improving Professional Image on Instagram - Sandra Alfiani; Sri Hastjarjo; Sudarmo, Sudarmo (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research delves into the profound impact of technological advancements in photography, particularly with the widespread use of smartphones. Focusing on the convergence of mobile phone technology and photography, the study explores the self-branding strategy employed by mobile photographers to cultivate a professional image on Instagram. Utilizing a descriptive phenomenological method, the research highlights key strategies such as showcasing skills, improving profile quality, individualizing the brand, expanding online presence, and fostering client relationships. The findings emphasize the significance of Instagram as a platform and unveil a comprehensive process involving content conceptualization, target selection, and consistent content delivery for successful self-branding in the mobile photography realm.